PENUTUPAN PINTU IJTIHAD: SATU KAJIAN SEMULA - Mohd Nor, Amir Husin (Jurnal Syariah, 2019)
This article highlights some legal arguments on the importance of opening the closure of ijtihZui in present muslim society. It also discusses the misunderstanding of the popular notion regarding the discontinuity of ijtihad among the muslim society.